The Effect of Leadership, Work Communication and Work Motivation on Employee Performance at Linggang Bigung District Office, West Kutai Regency - Yohanes Liku; Ida Bagus Made Agung Dwijatenaya; Musmuliadi Musmuliadi (Publikasi Indonesia, 2022)
The scope of this study aims to determine the effect of leadership and work communication on employee performance at the Linggang Bigung sub-district office, West Kutai Regency. This type of research is an associative quantitative research with the work unit under study being all employees of the Linggang Bigung Sub-district Office, West Kutai Regency. This study includes a population study with a population of 35 respondents. The validity and reliability test questionnaire before conducting research data. The test equipment used in this study uses classical assumptions, the method of data analysis used is multiple regression analysis, t test and f test are also carried out including the coefficient of determination test. The results showed that leadership partially had a positive and significant effect on the performance of the Linggang Bigung sub-district office employees, West Kutai Regency, work communication partially had a positive and significant effect on the performance of the Linggang Bigung sub-district office employees, West Kutai Regency and both variables had a positive and significant effect simultaneously. on the performance of the Linggang Bigung sub-district office employee, West Kutai Regency. from the results of the coefficient of determination test also obtained a value of 0.841 or 84.1%, meaning that leadership and work communication are able to explain the effect on employee performance while the remaining 15.1% is influenced by other variables not examined in this study.